Venezuelan migration in Peru: Short-term adjustments in the labor market - Fernando Morales; Martha Denisse Pierola (Inter-American Development Bank (IDB), 2020)
The Venezuelan migration to Peru has been growing at fast speed since 2016 reaching a peak in 2018. Using a panel that allows us to control for individual effects, we study the heterogeneous short-term responses to the inflow of Venezuelan migrants in terms of employment, informality and earnings of Peruvian workers during 2008-2018. We find that a 1 pp increase in the share of Venezuelan migrants in Peru is associated with: a) a 1.5 pp increase in the probability of being employed for workers with tertiary education in the non-service sector; b) a 1 pp decrease in the probability of having an informal job for workers with tertiary education in the non-service sector; and c) a 3.2 percent decrease in real monthly earnings for workers with secondary education and a formal job in the service sector.
Keywords: F22; J21; J24; J30; J46; J61; R23; 330; Venezuelan migration; labor supply shock